Implementation of Digital Character Education to Reduce Cyberbullying: A Case Study at Muhammadiyah Limbung Senior High School in Indonesia - Nurhayati Nurhayati; Beti Istanti Suwandayani; Lud Waluyo (Universitas PGRI Yogyakarta, 2026)
This study aims to describe the implementation of digital-based character education as a strategy to reduce cyberbullying at Muhammadiyah Limbung Senior High School in Indonesia. The research employed a qualitative case-study design. Data collection techniques included observation, in-depth interviews, and documentation, with teachers and students as the research subjects. The findings indicate that digital-based character education was designed through a strategic planning process that involved selecting core character values, using relevant digital media, and adopting participatory learning approaches. Implementation was carried out by integrating character values into digital learning activities, such as anti-cyberbullying campaigns, digital ethics reflections, and student engagement with educational content on social media platforms. Supporting factors for the program’s success included the availability of digital infrastructure, teacher competence, supportive school policies, and parental participation. Conversely, inhibiting factors comprised students’ low digital ethics literacy, limited access to technology at home, insufficient teacher training, and minimal parental involvement. The study concludes that digital-based character education effectively fosters students’ ethical awareness and behavior in the online environment and significantly reduces incidents of cyberbullying within the madrasah. Keywords: character education, cyberbullying, digital ethics, digitalization of education